Kedudukan Hadis Ahad Menurut Imam Al-Syafi’i - Masykur Hakim (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2003)
This paper aims to highlight the capacity of Imam al-Shafi’i as a hadith scholar, with a specific focus on his views regarding the status of hadith ahad and its use as evidence. Imam al-Shafi’i, as one of the prominent imams in Islamic history, made significant contributions to the development of hadith science and usul al-fiqh. His views on hadith ahad—i.e., hadiths narrated by only one or a few transmitters—are crucial for understanding the methodology of evaluating and accepting hadith within Islamic tradition. This study will outline Imam al-Shafi’i's perspective on the status of hadith ahad within the context of Islamic law and its acceptance as a valid source of legislation. Imam al-Shafi’i recognized the value of hadith ahad in certain situations and contexts, and his opinions often serve as a reference in determining whether hadith ahad can be used as a legal basis. The paper will also discuss how Imam al-Shafi’i assesses the evidentiary strength of hadith ahad and the principles he employs in evaluating its authenticity and authority. Through text analysis and historical interpretation, this study will explore Imam al-Shafi’i's contributions to the understanding of hadith ahad and its implications for Islamic legal practice. Additionally, it aims to highlight the relevance of Imam al-Shafi’i’s views in the modern context and how his perspectives can enrich hadith studies and contemporary Islamic legal applications. This paper is expected to provide deep insights into Imam al-Shafi’i’s position in hadith science and his role in establishing the criteria for accepting hadith ahad as evidence in Islamic law.